Antimicrobial Activity of Cherry Stem Extracts (Prunus sp.) from the Souk Ahras Region-Algeria - - Bouteraa Oussama; Younsi Louey (My University, 2026)
Antimicrobial resistance represents one of the most pressing public health challenges of the twenty-first century, with over 1.27 million deaths directly attributed to resistant infections worldwide in 2019. The development of new therapeutic alternatives from natural sources has become a scientific priority, particularly in regions such as northeastern Algeria, where plant biodiversity is high and pharmaceutical resources are limited. The present study investigates, for the first time, the antibacterial activity of ethanolic extracts prepared from the peduncles of four Prunus sp. cherry cultivars: Bigarreau Burlat (V1), Bigarreau Napoléon (V2), Sunburst (V3) and a local late-ripening landrace (V4) cultivated across the altitudinal gradient of the Souk Ahras region (500–1,200 m, northeastern Algeria).Peduncles were shade-dried, ground to a fine powder and extracted by maceration in 95% ethanol (1:10 w/v, 48 hours, 40–50 °C), followed by concentration using a rotary evaporator at 40 °C. Antibacterial activity was assessed against Staphylococcus aureus (ATCC 25923) and Pseudomonas aeruginosa (ATCC 27853) using the agar well diffusion method and broth microdilution for minimum inhibitory concentration (MIC) determination. Antibacterial testing demonstrated clear inhibitory activity against Pseudomonas aeruginosa, with maximum inhibition zone diameters of 28.9 mm (V1), 30.8 mm (V2), 26.1 mm (V3) and 30.2 mm (V4) and MIC values of 25% (V1), 50% (V2), 25% (V3) and 75% (V4), comparable to published benchmarks from Bosnian, Portuguese and Turkish studies. No activity was observed against Staphylococcus aureus, with no inhibition zones detected (0 mm for all four cultivars), consistent with the organism's intrinsic multidrug-resistance mechanisms. This study fills a documented gap in global scientific studies and demonstrates that cherry peduncles from northeastern Algeria represent a locally available, agriculturally wasted resource with genuine natural antibacterial potential. ----------------------------------------------------------------------------------------------------------------------------------------------------------------------- تشكل مقاومة مضادات الميكروبات أحد التحديات الصحية العامة الأكثر إلحاحًا في القرن الحادي والعشرين، حيث تم تسجيل أكثر من 1.27 مليون حالة وفاة مرتبطة مباشرة بالعدوى المقاومة في جميع أنحاء العالم في عام 2019. أصبح تطوير بدائل علاجية جديدة من أصل طبيعي أولوية علمية، خاصة في مناطق مثل شمال شرق الجزائر، حيث تكون التنوع البيولوجي النباتي مرتفعًا والموارد الصيدلانية محدودة.تقيّم هذه الدراسة، للمرة الأولى، النشاط المضاد للبكتيريا لمستخلصات الإيثانولية المحضرة من أعناق أربع أصناف من شجرة الكرزBigarreau Burlat. Prunus sp. (V1)،Bigarreau Napoléon (V2)، Sunburst(V3)ونمط محلي ناضج متأخر(V4)المزروعة على طول المرتفعات في منطقة سوق أهراس (500-1200 م، شمال شرق الجزائر(. اين تم تجفيف أعناق الكرزفي الظل، وطحنها إلى مسحوق ناعم، واستخراجها بالتنقيع في الإيثانول بنسبة 95% (نسبة 1:10 وزناً/حجماً، لمدة 48 ساعة، عند 40-50 درجة مئوية)، ثم تركيزها باستخدام مبخر دوار عند 40 درجة مئوية. تم اختبار النشاط المضاد للبكتيريا ضدStaphylococcus aureus (ATCC 25923) وPseudomonas aeruginosa(ATCC853)عن طريق الانتشار على الآبار في الآغار والتخفيف الميكروبي في المحلول لتحديد التركيز الأدنى المثبط (CMI). حيث أظهرت اختبارات مضادات البكتيريا نشاطًا مثبطًا واضحًا ضدPseudomonas aeruginosa،مع أقصى أقطار لمنطقة التثبيط تبلغ 28.9 مم (V1)، 30.8مم (V2)، 26.1مم (V3) و30.2 مم (V4)، وقيم MIC تبلغ %25 (V1)، 50% (V2)، 25% (V3) و%75 (V4)، مقارنةً بالمعايير المنشورة من الدراسات البوسنية، البرتغالية، والتركية. لم يتم ملاحظة أي فعالية ضد Staphylococcus aureus ، حيث لم يتم تسجيل أي مناطق تثبيط (0 مم لجميع الأصناف الأربعة)، وهو ما يتماشى مع آليات مقاومة الأدوية المتعددة الكامنة في الكائن الحي.تسدّ هذه الدراسة ثغرة موثقة في الدراسات العلمية العالمية، وتُثبت أن أعناق ثمار الكرز من شمال شرق الجزائر تُشكِّل موردًا محليًا متاحًا ومهدرًا زراعيًا يمتلك إمكانات حقيقية مضادة للبكتيريا ----------------------------------------------------------------------------------------------------------------------------------------------------------------------- La résistance aux antimicrobiens constitue l'un des défis de santé publique les plus urgents du XXIe siècle, avec plus de 1,27 million de décès directement attribués aux infections résistantes dans le monde en 2019. Le développement de nouvelles alternatives thérapeutiques d'origine naturelle est devenu une priorité scientifique, en particulier dans des régions telles que le nord-est de l'Algérie, où la biodiversité végétale est élevée et les ressources pharmaceutiques limitées. La présente étude évalue, pour la première fois, l'activité antibactérienne des extraits éthanoliques préparés à partir des pédoncules de quatre cultivars de cerisier Prunus sp. : Bigarreau Burlat (V1), Bigarreau Napoléon (V2), Sunburst (V3) et un écotype local à maturation tardive (V4) cultivés le long du gradient altitudinal de la région de Souk Ahras (500-1200 m, nord-est de l'Algérie). Les pédoncules ont été séchés à l'ombre, broyés en poudre fine et extraits par macération dans l'éthanol à 95 % (rapport 1:10 p/v, 48 heures, 40-50 °C), puis concentrés à l'aide d'un évaporateur rotatif à 40°C. L'activité antibactérienne a été testée contre Staphylococcus aureus (ATCC 25923) et Pseudomonas aeruginosa (ATCC 27853) par méthode de diffusion sur gélose en puits et microdilution en bouillon pour déterminer la concentration minimale inhibitrice (CMI). Les tests antibactériens ont montré une activité inhibitrice claire contre Pseudomonas aeruginosa, avec des diamètres maximaux des zones d'inhibition de 28,9 mm (V1), 30,8 mm (V2), 26,1 mm (V3) et 30,2 mm (V4), et des valeurs de CMI de 25 % (V1), 50 % (V2), 25 % (V3) et 75 % (V4), comparables aux références publiées dans des études bosniaques, portugaises et turques. Aucune activité n'a été observée contre Staphylococcus aureus, aucune zone d'inhibition n'ayant été détectée (0 mm pour les quatre cultivars), ce qui est cohérent avec les mécanismes de multirésistance intrinsèque de cet organisme. Cette étude comble une lacune documentée dans les études scientifiques mondiale et démontre que les pédoncules de cerise du nord-est de l'Algérie représentent une ressource locale, gaspillée dans l'agriculture, avec un véritable potentiel antibactérien naturel.
Keywords: antibacterial activity; cherry peduncles; ethanolic extract; minimum inhibitory concentration; northeastern Algeria.; نشاط مضاد للبكتيريا؛ أعناق الكرز؛ مستخلص إيثانولي؛ التركيز المثبط الأدنى؛ شمال شرق الجزائر.; activité antibactérienne; pédoncules de cerise; extrait éthanolique; concentration minimale inhibitrice; nord-est de l'Algérie.